The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/bse.2838
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable development in aviation logistics: Successful drivers and business strategies

Abstract: Firms looking to implement sustainable development confront the problem of choosing among myriad options. To help them overcome it, this study develops two-stage data-driven analytics aimed at establishing which alternatives for sustainable development are most likely to succeed, based on careful scrutiny of sustainableaviation cases. Specifically, it first ascertains the factors that are most critical to aviation logistics in general and then goes on to identify the vital drivers of successful sustainable dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…Planes need a specific weight for take‐off and landing and, even if empty, need to charge enough fuel to consider all those aspects. In this way, if code‐sharing promotes more complete flights, the intuitive thought would be to consider that this operational efficiency is also transferred into environmental efficiency (Ryerson et al, 2014; Simaiakis et al, 2014), resulting in less air congestion in peak times and improved on‐time departures and arrivals (Yimga, 2017), thus contributing to environmental sustainability (Wu & Yang, 2021). This eco‐efficiency implies reducing the ecological impact to secure the availability of resources to be used in the future (Ehrenfeld, 2005).…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…Planes need a specific weight for take‐off and landing and, even if empty, need to charge enough fuel to consider all those aspects. In this way, if code‐sharing promotes more complete flights, the intuitive thought would be to consider that this operational efficiency is also transferred into environmental efficiency (Ryerson et al, 2014; Simaiakis et al, 2014), resulting in less air congestion in peak times and improved on‐time departures and arrivals (Yimga, 2017), thus contributing to environmental sustainability (Wu & Yang, 2021). This eco‐efficiency implies reducing the ecological impact to secure the availability of resources to be used in the future (Ehrenfeld, 2005).…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…Consumers can achieve this through engagement with e‐commerce, which provides a safer alternative than in‐store shopping. Wu and Yang ( 2020 ) looked into a logistics problem and found that many things are good for the environment in the aviation industry.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Sustainable solutions depend on individual or group knowledge, as well as a growing understanding of different important topics such as climate change, toxic emissions, pollution and social inequalities (Mitchell & Walinga, 2017). It is a challenge to determine the most appropriate environmental sustainability solutions among the numerous feasible solutions (Wu & Yang, 2021). The sustainability approaches change according to the growing awareness of firms' responsibility towards a more sustainable business culture (Giannakis & Papadopoulos, 2016).…”
Section: Linking Wicked Problem Complexities With Sscmmentioning
confidence: 99%